The Moderating Role of Green Budget Tagging on Budgeting Practices and Fiscal Policy Sustainability in Ghana’s Local Government - Shaibu Awudu; Nugraha Nugraha; Chairul Furqon; Maya Sari; Ayu Krishna Yuliawati (Khazanah Sosial, 2025)
This study investigates how green budget tagging moderates the relationship between Green Budgeting Practices and fiscal policy sustainability in Metropolitan, Municipal, and District Assemblies (MMDAs). Using a quantitative research approach and multiple regression analysis, the study examines how Green Budget Practices influence Fiscal Policy Sustainability. Key findings reveal that while Climate Change Adaptation and Mitigation, Waste Management, Renewable Energy Development, and Natural Resource Conservation positively impact Fiscal Policy Sustainability, Sustainable transport does not directly affect fiscal policy sustainability. Moreover, Green budget labelling interacts negatively with Budget Practices and Fiscal Policy Sustainability. Net impacts indicate that environmental issues still support fiscal policy sustainability. Policymakers must address the issue of how green budget labelling has inadvertently harmed significant environmentally sustainable activities, and diligently design and implement a green budget labelling framework that balances ecological objectives with economic prudence. To ensure that environmental initiatives do not inadvertently compromise fiscal sustainability, they should also enhance communication between the departments responsible for environmental and fiscal policy management. This study makes a significant contribution to the implications of green budget labelling in Ghana. It provides policymakers with critical information regarding the impact of green budgeting on fiscal policy and offers recommendations for its implementation. This research addresses a gap in the literature, contributes to the growing discourse on sustainable fiscal policies, and offers a practical framework for other local governments to emulate more effectively align their environmental issues and economic objectives.